You are my home - Williams, Vanessa L.; Chayanne; Thomas, Keith; Sony Music Entertainment (New York : Sony Music Entertainment, 1998)
Contains three versions of the song You Are My Home taken from the Dance With Me movie.
CD 1 : Radio edit -- Album version -- Spanglish version.
Koleksi Khas Wiramanja.
Keywords: Film soundtracks; Motion pictures and music